Enhancing Student Engagement and Critical Thinking through the AERO Staged Pedagogy in EFL Higher Education - Umiyati Jabri; Ismail ismail; Ita Sarmita Samad (Majesty Journal, 2025)
This study investigates the implementation of the AERO (Activation → Exploration → Reflection → Outcome) framework as a staged pedagogy to enhance student engagement and critical thinking skills among English as a Foreign Language (EFL) learners at Universitas Muhammadiyah Enrekang, Indonesia. Employing a mixed-method design with a pre-experimental one-group pretest–posttest approach, the research involved 22 undergraduate students enrolled in an academic writing course. Quantitative data were collected through a student engagement questionnaire and a critical thinking test adapted from the Watson–Glaser Critical Thinking Appraisal (WGCTA), while qualitative data were obtained from classroom observations and focus group discussions (FGD). Results revealed moderate to high engagement across cognitive, affective, and behavioral dimensions, supported by qualitative evidence of increased participation, motivation, and collaboration during the staged activities. Although the improvement in critical thinking test scores (M_pre = 3.73; M_post = 4.27) was not statistically significant (p > .05), qualitative findings demonstrated notable cognitive shifts toward analytical, evaluative, and reflective reasoning. The AERO stages fostered progressive scaffolding, transferring learning responsibility from teacher to student while promoting reflective, evidence-based argumentation. Theoretically, this study contributes to EFL pedagogy by linking three engagement dimensions with four critical thinking subskills within a coherent process model. Practically, AERO offers a replicable design framework for fostering student-centered learning, reflective inquiry, and critical literacy in EFL classrooms. Recommendations for future research include extending the intervention period and exploring AERO’s application in digital or hybrid learning contexts.